Burmese crafts - Fraser-Lu, Sylvia (Oxford University Press, 2005)
In this work, Sylvia Fraser-Lu introduces the reader to the scope and beauty of Burmese crafts by exploring the historical background, the foundations of Burma's artistic traditions, and the temple and pagoda arts of brick, stucco, sculpture, and painting. She then presents a systematic survey of the development and evolution of Burma's major crafts, such as bronze and ironwork, wooden architecture, wood-carving, gold, silver, and jewelry, ceramics, lacquer, textiles and costume, books, paper, baskets, mats, and umbrellas